Group support system and explanatory feedback: An experimental study of mitigating halo effect - Intiyas Utami; Sutarto Wijono (Universitas Hayam Wuruk Perbanas, 2015)
Comprehensive assessment potentially leads to halo effect that will affect accuracy of auditors’ decision-making process. Biased initial audit decision will potentially influence final audit decision. It is there-fore necessary to mitigate halo effect that is the consequence of auditors’ good impression on clients’ initial condition. This re-search aims to empirically show that halo effect can be mitigated by explanatory feedback and Group Support System (GSS). The researchers experimentally mani-pulate explanatory feedback and GSS using online web-site. The subjects are stu-dents who have already taken auditing courses. The results show that: 1) explanato-ry feedback can mitigate halo effect so that audit decision will be more accurate 2) GSS can also mitigate halo effect 3) explanatory feedback and GSS are the best me-thods to mitigate halo effect.